Medical Screening Through Community-Based Social Service Programs for Sustainable Public Health Improvement Strategy in Cikeas Udik, Bogor Regency - Liana, Duta; Mulyani, Erry Yudhya; Maratis, Jerry; Fauziah, Nuraini; Susilawati, Tati; Ulli, Meilanda Metawati; Anggraeni, Dwi Puspitasari Anggita; Triyani, Endang; Puri, Ratna; Noviana, Ulfa; Saputro, Eko Wahyu Irvan; Dewi, Defi Chintya; Frisma, Istiqo; Stephanie, Maria; Husnan, Faidh; Susanto, Prandika; Julyta, Dwi Meutia; Astika, Fannysa; Puspitaningrum, Ratri (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Epidemiological transition in Indonesia has been marked by rising prevalence of non-communicable diseases (NCDs), including hypertension, diabetes mellitus, and metabolic disorders, which often remain undetected at early stages. Limited access to healthcare services and inadequate early detection at community level exacerbate risk of complications and increase public health burden. This activity to improve community health status through social service–based health screening and treatment as an effort for early detection and initial management of health problems in Cikeas Udik, Bogor. This activity employed an integrated approach comprising health education, screening, basic medical, and referral. Program was conducted on September 13, 2025, involving 105 adult and elderly participants. Health assessments included medical history taking, blood pressure measurement, random blood glucose testing, cholesterol and uric acid examinations, followed by medication provision according to clinical indications and referral when necessary. Most participants were female (75.2%) and adult age group (70.5%). Hypertension was the most frequently identified diagnosis (37.1%), followed by acute respiratory infections and dyspepsia. Proportion of participants demonstrated elevated levels of blood glucose, cholesterol, and uric acid. Five main categories of medications were analgesics, antihypertensive agents, oral antidiabetic, antacids, and multivitamins. Community-based health social service activities are effective in improving access to healthcare services, facilitating early detection of NCDs, and providing medical treatment and health education. This approach has the potential to contribute to sustainable improvements in community health through integrated, community-oriented healthcare services. Keywords: Social Service, Health Screening, Non-Communicable Diseases, Community Health Services, Public Health.